Room-temperature quasi-catalytic hydrogen generation from waste and water - Wu, Hongguo; Zhang, Li-Long; Wang, Junqi; Jiang, Yiyuan; Li, Hu; Sudarsanam, Putla; Yang, Song (Green Chemistry, 2021)
A solvation-driven catalyst-free H-2 generation system from water and various waste hydrosilanes at room temperature was developed, with good to quantitative H-2 yields in minutes. Using a green solvent is found to promote the strong coordination of proton carriers with hydrosilane to liberate H-2 based on molecular dynamics simulations. Theoretical calculations clarify that OH(-)in situ generated from H2O enabled by solvation is favorable for activating the Si-H species of hydrosilane, and the in situ formed Si-OH interacts more effectively with the adjacent remaining Si-H, both contributing to the overall enhanced H-2 generation. Moreover, the overall life-cycle impacts of the developed system are less than those of industrial H-2 production processes, especially in ozone layer depletion and abiotic depletion resources - fossil fuels. This protocol realizes the potential of efficiently producing H-2 from waste and water, and opens a new avenue to alleviate petroleum consumption.

Protophilic solvent-impelled quasi-catalytic CO2 valorization to formic acid and N-formamides - Wu, Hongguo; Li, Hu; Zhao, Wenfeng; Sudarsanam, Putla; Yang, Song (Fuel, 2022)
As a low-price and luxuriant C1 sustainable resource, CO2 has the privilege of synthesizing hydrogen carriers and valuable chemicals. However, expensive metallic and organic catalysts are often indispensable for going on wheels of the relevant reaction processes. In this work, a protophilic solvent-impelled quasi-catalytic system was developed for efficient synthesis of formic acid and various N-formamides with high yields of 76-94% via reductive CO2 functionalization under mild reaction conditions (50 ?). Direct activation of the liquid hydrosilane toward the reduction of CO2 enabled by DMSO with optimum basicity/protophilicity is the predominant reaction route among the examined interaction models, while carbonic acid potentially derived from excessive CO2 and residual water inhibits the reaction, as explicitly disclosed by theoretical calculations and isotope labeling experiments. In addition, the in situ formed O-formyl species is conductive to the cascade CO2 reduction steps, which remarkably facilitated the overall quasi-catalytic upgrading process.
Keywords: CO2 utilization; Formic acid; Green energy; Nitrogenous chemicals; Quasi-catalysis